Environmental science : - Enger, Eldon D. (McGrawHill Higher Education, 2006)
This book discusses environmental issues. Its content is devided into 19 chapters which have the same approach. Chapters give a historical perspactive, appreciate economic and political realities, recognize the role of differenct social experiences and ethical backrounds and itegrate these with ths science that describes the nature world and how people affect it